PRAKTIK TRADISI MOMPOPALIA BALA’ PADA KENDARAAN BARU DI DESA BATU HITAM PERSPEKTIF URF - Listanto Ndeo, Virgiawan; Mubakkirah, Fadhliah; B, M. Taufan (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
In the community of Batu Hitam Village, Nuhon Subdistrict, Banggai Regency, many customs and traditions are still preserved, upheld, believed in, and developed, one of which is the Mompopalia Bala’ Tradition. The Mompopalia Bala’ Tradition, or ritual to ward off misfortune, has been practiced in this region for a long time. This tradition is held as an expression of gratitude to the Creator for the successes achieved. This research aims to understand and examine the practice and the ‘Urf perspective on the Mompopalia Bala’ tradition in Batu Hitam Village. To achieve this goal, an empirical legal research method with an interdisciplinary approach was used. The research was conducted in Batu Hitam Village, Nuhon Subdistrict, Banggai Regency, through field observations, interviews with traditional leaders, religious leaders, and community figures, and documenting the interview process as well as the execution of the Mompopalia Bala’ tradition. The results of this research show that the Mompopalia Bala’ tradition begins with determining the time and day for bringing in the new vehicle (Molio jamsinanu maima), storing the new vehicle for three days (Monguna kendraan anuoli), and concludes with a prayer recitation over water and the sprinkling of the water onto the new vehicle (Mondudu’i kendraan anu sala’je ingoli). From the perspective of ‘Urf, the Mompopalia Bala’ Tradition in Batu Hitam Village, in terms of its meaning, falls under Urf Al-Khas, and in terms of its form, it is included in Al-‘Urf Al-Fi’li, while from the aspect of being considered a legal basis, it falls under ‘Urf Shahih.